Positive Self-Talk and Self-Confidence Among Elementary Students: A Quasi-Experimental Study in Gowa - Gilang Tri Prayogo Yusuf; Sitti Ariqah Azka Haris; Vania Elysie Juscine; Ummu Asy-syifa Amalia; Winda Salman; A. Muh. Raihan B. Amir; Wisda Via Nurfallah; Gyanesh Kumar Tiwari (Jurnal Psikologi Teori dan Terapan, 2026)
Background: Low self-confidence in upper elementary school can undermine academic engagement and socio-emotional adjustment, highlighting the need for school-based interventions. Objective: This study examined the effectiveness of a positive self-talk intervention to enhance self-confidence among fifth-grade students. Method: Using a one-group pretest–posttest design, seven students with low-to-moderate self-confidence were identified through classroom observations and teacher interviews. Four structured sessions employed play-based activities, storytelling, and guided practice to foster cognitive reinterpretation. Self-confidence was measured using the Self-Confidence Assessment Instrument before and after the intervention. Results: All seven participants showed improvement, with group-level analysis indicating statistically significant change (Sign Test, p = .016, Cohen's d = 2.61), though the large effect size should be interpreted cautiously given the small sample (n = 7) and absence of a control group. Conclusion: The intervention appears practical and potentially promising for enhancing self-confidence in similar school contexts. Findings provide preliminary support for brief cognitive interventions in schools, while underscoring the need for replication through controlled studies with larger samples. Abstrak Latar Belakang: Rendahnya self-confidence pada siswa sekolah dasar kelas tinggi dapat mengganggu keterlibatan akademik dan penyesuaian sosial-emosional, sehingga diperlukan intervensi berbasis sekolah. Tujuan: Penelitian ini menguji efektivitas intervensi self-talk positif untuk meningkatkan self-confidence pada siswa kelas lima. Metode: Menggunakan desain pretest–posttest satu kelompok, tujuh siswa ber-self-confidence rendah hingga sedang diidentifikasi melalui observasi kelas dan wawancara guru. Empat sesi terstruktur menggunakan aktivitas berbasis bermain, bercerita, dan latihan terpandu untuk memfasilitasi reinterpretasi kognitif. Self-confidence diukur menggunakan Self-Confidence Assessment Instrument sebelum dan sesudah intervensi. Hasil: Ketujuh partisipan menunjukkan peningkatan, dengan analisis tingkat kelompok mengindikasikan perubahan yang signifikan secara statistik (Sign Test, p = 0,016, Cohen's d = 2,61), meskipun effect size yang besar ini perlu diinterpretasikan secara hati-hati mengingat sampel yang kecil (n = 7) dan ketiadaan kelompok kontrol. Kesimpulan: Intervensi ini tampak praktis dan berpotensi menjanjikan untuk meningkatkan self-confidence dalam konteks sekolah serupa. Temuan ini memberikan dukungan awal bagi intervensi kognitif singkat di sekolah, serta menegaskan perlunya replikasi melalui studi terkontrol dengan sampel lebih besar.